Pengaruh Tingkat Pendapatan Terhadap Jumlah Penduduk Miskin: Studi Kasus di Kota Gorontalo - Mohamad, Nurdin; Thalib, Heru Z; Yusuf, Daud; Faridawaty, Waode; Dunggio, Iswan; Rahim, Sukirman (CV. Ulil Albab Corp, 2024)
This study analyzes the impact of income levels on the number of poor people in Gorontalo City, which, despite experiencing economic growth, still faces significant poverty issues. Gorontalo City heavily relies on the agriculture and fisheries sectors, which are vulnerable to climate change and market fluctuations, causing the income of the majority of its population to remain low and unstable. Previous studies have shown that although income has increased, high social and economic disparities have exacerbated poverty. In this study, we used simple linear regression analysis, which revealed a moderate relationship between income levels and the number of poor people, although the regression model has a low explanatory power (R-squared of 0.2160). The results indicate that, despite income growth, income inequality remains the primary factor contributing to the high poverty rate. The implications of these findings highlight the need for policies that focus more on income redistribution and the empowerment of the informal sector to reduce social inequality and improve the well-being of the people in Gorontalo sustainably